Free tools for paraphasing: to use or not to use / Ho Chui Chui - Ho, Chui Chui (Universiti Teknologi MARA, Kedah, 2023)
Paraphrasing is generally considered a challenging skill to acquire but it is a necessity in academic writing. With the advent of technology, a plethora of applications both free and premium are now available to authors looking for shortcuts. This article reports the findings of a small-scale study to assess a free paraphrasing tool, the QuillBot paraphraser and ChatGPT, the artificial intelligence assistant that can be used to paraphrase texts. A paragraph from Purdue Online Writing Lab was extracted to generate the paraphrases. Results indicate that QuillBot generally failed to paraphrase original texts appropriately as it basically substituted words with synonyms with few to no structural changes. Users of the tool would be considered as patchwriting or plagiarising although the original author was cited. Although ChatGPT was more impressive, it also had limitations such as providing incorrect citations and nonexistent sources. Users should be aware of the pitfalls of relying on these free tools and instead write their own paraphrases to avoid the potential risk of committing academic dishonesty.